Justice, Mediation, and Kalosara Custom of the Tolaki Community in Southeast Sulawesi from the Perspective of Islamic Law - Kamaruddin, Kamaruddin; Iswandi, Iswandi; Yaqub, Andi; Mahfiana, Layyin; Akbar, Muh. (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The existence of customary law has been less a concern as a source in the law enforcement process for law enforcers. The Tolaki community in Southeast Sulawesi has a custom capable of resolving legal disputes called kalosara. This study aims to examine the customary role of the Kalosara in resolving land disputes to create justice and social order in society. This empirical legal study used the sociological theory of law and benefit in Islamic law. Data were collected by means of in-depth interview and literature review. The results of the study revealed that the Kalosara that has become a customary law or living law in society has played a role in resolving cases through mediation. The Kalosara customarily carried out through a mediation process has been able to mitigate internal cases of the indigenous people. Dispute resolution resolved in terms of land cases has also succeeded in creating social order in society. The philosophical principles in the Kalosara consist of ate pute penao moroha (chastity and justice), the values that are able to bind the parties to the disputes in a customary way to create justice. Theoretically, the social function of the customary law in society is to realize social harmonization so that disputes and conflicts can be avoided. In the context of the Islamic law, creating harmony and social order in society is one of the main goals.